Recent Trust Management Models for Secure IoT Ecosystem - Rana, Kajol; Singh, Ajay Vikram; Vijaya, P. (International Journal of Intelligent Systems and Applications in Engineering, 2022)
The emotional component of trust is crucial in the rapidly evolving world of computers. With a focus on distributed Trust Management systems, a variety of Trust Management frameworks and models have recently been developed for the Internet of Things (IoT). IoT systems may offer considerable advantages across a wide range of application sectors. These fields span everything from smart grid technology to home automation, environmental monitoring, and healthcare. However, there are numerous security concerns with the IoT, including challenges with trust management, key management, identification, and availability. The Internet of Things offers a realistic solution for threat management called "security by trust" (IoT). For symbiotic applications on the IoT stage, there is currently no clear-cut trust management framework. A framework’s nodes’ dependability should be evaluated in order to estimate the trust using the proper bounds. The parametrization of trust is not explicitly spelled out in existing models. Likewise, most existing models do not adequately depict trust erosion. Furthermore, trust recommendations are frequently given incorrect weights based on past trust, which increases the impact of poor recommendations. In this review paper, we’ll cover about various trust models and how they affect Internet of Things security.